Impact of temperature and airflow rate on the removal of organic pollutants and inorganic pollutants in the biological treatment process - M. Muloiwa; M.O. Dinka; S. Nyende-Byakika (South African Journal of Chemical Engineering, 2023)
The purpose of this study was to analyse the impact of temperature and airflow rate on the removal of COD and ammonia. This study showed for the first time that temperature has a significant impact on the removal of COD and ammonia compared with airflow rate. The impact of temperature and airflow rate on COD and ammonia removal was analysed using R², linear regression line, and ANOVA test. The results of the study showed that the highest COD removal was 157 mg/l measured at a temperature of 35 °C and airflow rate of 10 l/min. The highest ammonia removal was 15.9 mg/l measured at a temperature of 32.5 °C and airflow rate of 20 l/min. The results showed that when temperature increased, COD and ammonia removal increased linearly. R² values were 66.6% and 59.5% for COD and ammonia removal respectively. Linear regression lines were positive 2.69 mg/l and 0.3573 mg/l respectively. The ANOVA test confirmed that temperature had a significant impact on both COD (P 0.03 < 0.05) and ammonia removal (P 0.000 < 0.05). When airflow rate increased, COD and ammonia removal decreased. R² values were 44.7% and 32.5% respectively. Linear regression lines were negative 0.8343 and 0.084 respectively. The ANOVA test confirmed that airflow rate had no significant impact on both COD (P 0.525 > 0.05) and ammonia removal (P 0.902 > 0.05). The optimum operating temperature and airflow rate were 32.5 °C – 35 °C and 5 l/min–10 l/min respectively.